Respostas
respondido por:
0
Resposta:
S= ( 1 )
Explicação passo-a-passo:
- x² + 2x - 1 = 0
A= - 1
B= 2
C= - 1
∆= b² - 4ac
∆= 2² - 4 • ( - 1) • ( - 1)
∆= 4 - 4
∆= 0
x= - b ± √∆/2a
x= - 2 ± √0 / 2 • (-1)
x= - 2 ± 0 / - 2
x' e x"= - 2 ± 0/- 2 = - 2/-2 = 1
S= (1 )
respondido por:
0
Resposta:
1
Explicação passo-a-passo:
Arrumar a equação,
número pra um lado e letras pro outro.
após é só resolver.
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás